Spectroscopic confirmation of a gravitationally lensed Lyman-break galaxy at z[C ii] = 6.827 using NOEMA. Issue 1 (4th March 2022) - Molyneux, S J; Smit, R; Schaerer, D; Bouwens, R J; Bradley, L; Hodge, J A; Longmore, S N; Schouws, S; van der Werf, P; Zitrin, A; Phillips, S
ABSTRACT: We present the spectroscopic confirmation of the brightest known gravitationally lensed Lyman-break galaxy in the Epoch of Reionization (EoR), A1703-zD1, through the detection of [C ii ] 158 μ m at a redshift of z = 6.8269 ± 0.0004. This source was selected behind the strong lensing cluster Abell 1703, with an intrinsic luminosity and a very blue Spitzer /Infrared Array Camera (IRAC) [3.6]–[4.5] colour, implying high equivalent width line emission of [O iii ] + Hβ. [C ii ] is reliably detected at 6.1σ cospatial with the rest-frame ultraviolet (UV) counterpart, showing similar spatial extent. Correcting for the lensing magnification, the [C ii ] luminosity in A1703-zD1 is broadly consistent with the local L_[C II] –star formation rate (SFR) relation. We find a clear velocity gradient of 103 ± 22 km s^-1 across the source that possibly indicates rotation or an ongoing merger. We furthermore present spectral scans with no detected [C ii ] above 4.6σ in two unlensed Lyman-break galaxies in the Extended Groth Strip (EGS)-Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS) field at z ∼ 6.6–6.9. This is the first time that the Northern Extended Millimeter Array (NOEMA) has been successfully used to observe [C ii ] in a 'normal' star-forming galaxy at z > 6, and our results demonstrate its capability to complement the Atacama Large Millimeter/submillimeter Array (ALMA) in confirming galaxies in the EoR.